IMPLEMENTATION OF ISLAMIC GUIDANCE IN STUDENT’S MENTAL DEVELOPMENT - Khairuddin, Khairuddin (VISION, 2023)
This research aims to describe the implementation of Islamic guidance counseling  in the mental development of students at Madrasahs in Tanjung Balai City. This type of research is in the qualitative category with descriptive study methods. Data collection techniques using interviews, observation and document review. Then the data was analyzed using data reduction steps, data exposure, and drawing conclusions. In this case the data is checked using credibility, dependability, confirmability and transferability techniques. The results of this research indicate that the guidance and counseling services at the Tanjung Balai City madrasah in an effort to develop students' mental development are carried out well. This is characterized by (1) the Islamic activity program and mental development of students covering the areas of faith, morals, worship and muamalah; (2) stages of Islamic services in developing students' mental development, namely case identification, diagnosis, prognosis, therapy, evaluation and follow-up; (3) Islamic guidance and counseling services have an impact on students' ability to adapt at school and in society; (4) help students control themselves when hanging out (socially). Likewise, there are several obstacles in implementing Islamic in developing students' mental development, namely the minimum ratio of teachers to students in madrasas and limited guidance and counseling service facilities. The solution offered is the massive efforts of guidance and counseling teachers to take part in offline and online training and providing guidance and counseling facilities in madrasas.